Estudo da toxicidade do veneno bruto e detoxificado de Tityus serrulatus em ovinos produtores de antiveneno - Marina Guimar?es Ferreira (2013)
The aim of this study was to evaluate the toxicity of the crude venom of Tityus serrulatus and detoxified with glutaraldehyde in the production of scorpion antivenom in sheep, and study its neutralizing capacity in mice challenged with venom, as an alternative to replace the immunization protocol adopted in the country in production of antivenom. Twelve sheep, healthy, mean weight of 30 kg, were distributed into three groups (n=4): G1 (control), G2 (venom) and G3 (detoxified venom). It was used the immunization protocol (first cycle) adopted with six doses, three associated Freund's adjuvant, with space between them of 21 days and three with no adjuvant (booster) spaced three days. The G1 animals received the six immunizations with phosphate buffered saline (PBS) associated with Freund's adjuvant (1:1), while the other two groups received 0.5 mg of venom (G2) and detoxified venom (G3) , respectively, diluted in PBS, associated with the Freund adjuvant. The boosters counted with applying 1/3 of the initial dose, with only PBS. Before (time zero), 24 and 48 hours after immunization, all animals underwent clinical examinations, electrocardiograms and hematological and biochemical exams, dosing the AST, GGT, CK, LDH, urea, creatinine, glucose, pancreatic amylase, total protein and fractionated. Seven days after the first cycle of immunization, all animals were euthanized and gross and microscopic exams were evaluated. Any amendment macro or microscopic been seen in animal studies. Only animals of G2 showed mild clinical changes suggestive of the action of Tityus serrulatus. Regarding hematological profile, significant change in the number of leukocytes, neutrophils and eosinophils was observed in the three groups and the first three immunizations, in which we used Freund's adjuvant. There was a gradual increase in the enzyme GGT in animals of G3, suggesting a possible hepatotoxic discrete action of glutaraldehyde. Regarding the fractionated proteins, the fraction beta2, especially in groups 2 and 3, was increased in the booster immunizations, showing an inflammatory response. For neutralization assays it was used Swiss mice, with an average weight of 26 g distributed into 15 groups (n = 4): G1 to G4 (200 ul of antivenom control sheep + T. serrulatus venom), the G5 to G8 (200 ul of antivenom sheep immunized with crude + venom T. serrulatus venom), the G9 to G12 (200 ul of antivenom sheep immunized with detoxified venom+ venom of T. serrulatus), G13 (T. serrulatus venom), G14 (antivenom from the FUNED + venom of T. serrulatus) and G15 (pool serum of sheep receiving Freund's adjuvant without venom). We found rates of protection of 25%, 56.3% and 43.8% for sera from the G1, G2 and G3, respectively. It is concluded that the venom detoxified with glutaraldehyde may be used as immunogen, since animals of G3 showed no signs of toxicity while undergoing this immunization protocol and they were able to produce neutralizing antibodies venom of T. serrulatus in mice challenged.